POEMS-IN MEMORY OF CONTEMPORARIES OF MAQSUD SHAYKHZADEH (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
Maqsud Shaikhzoda's contribution to the prosperity of Uzbek literature, culture was deservedly honored by independent Uzbekistan and its government. A row school and streets are named after him. In this article, the work of Maqsud Shaykhzoda spoke about the importance of qualities such as courage, fairness, thoughtful thinking, popularism, expressed in the image of the heroes of the work in Uzbek literature.